Study on the suction capacity of disc-seal single screw pump used in energy recovery systems. (April 2020) - Wang, Zengli; Wang, Hao; Wang, Zongming; Li, Qiang; Wang, Jun; Feng, Quanke
Highlights: The suction volume mathematical model of disc-seal screw pump was established. The suction capacity calculation model of disc-seal screw pump was established. The suction capacity of disc-seal screw pump was investigated. Suction capacity varies in inverse proportion to density and rotation speed. Abstract: The disc-seal single screw pump (DSSP) is the key devices for liquid refrigerant conveying. However, there is little research on the suction capacity of this pump at present, which makes its application limited. In view of this, a mathematical model of the suction volume was established firstly based on the three-dimensional meshing theory. By using this model, the suction capacity calculation model was put forward, and the suction capacity and the impact mechanism of working parameters on it were investigated. The theoretical calculation results are in good agreement with the actual engineering data with the deviation not more than 6.5%. The results obtained by this validated model show that DSSP has abundant suction capacity with a suction capacity far more than 1 and the suction capacity varies in inverse proportion to density and rotation speed. All of these studies can provide theoretical basis for improving the performance of the DSSP.